Ontogeny of metabolic rate and red blood cell size in eyelid geckos: species follow different paths - Starostová, Zuzana; Konarzewski, Marek; Kozłowski, Jan; Kratochvíl, Lukáš (PloS one, 2013)
While metabolism is a fundamental feature of all organisms, the causes of its scaling with body mass are not yet fully explained. Nevertheless, observations of negative correlations between red blood cell (RBC) size and the rate of metabolism suggest that size variation of these cells responsible for oxygen supply may play a crucial role in determining metabolic rate scaling in vertebrates. Based on a prediction derived from the Cell Metabolism Hypothesis, metabolic rate should increase linearly with body mass in species with RBC size invariance, and slower than linearly when RBC size increases with body mass. We found support for that prediction in five species of eyelid geckos (family Eublepharidae) with different patterns of RBC size variation during ontogenetic growth. During ontogeny, metabolic rate increases nearly linearly with body mass in those species of eyelid geckos where there is no correlation between RBC size and body mass, whereas non-linearity of metabolic rate scaling is evident in those species with ontogenetic increase of RBC size. Our findings provide evidence that ontogenetic variability in RBC size, possibly correlating with sizes of other cell types, could have important physiological consequences and can contribute to qualitatively different shape of the intraspecific relationship between metabolic rate and body mass.
Keywords: Eyelids; Body Weight; erytrocyty; Erythrocytes; Lizards; oční víčka; Cell Size; druhová specificita; ještěři; velikost buňky; Basal Metabolism; Animals; Species Specificity; biologické modely; bazální metabolismus; tělesná hmotnost; zvířata; Models, Biological